Biocontrol of the black-spot disease pathogen (Alternaria alternata) in Dioscorea opposita by native endophytic bacterium Bacillus sp. E-Do8 - Chaochuang Li; Longlong Ma; Houmin Wang; Shunpeng Li; Ruifei Wang; Hao Zhang; Mingjun Li; Qingxiang Yang (BioControl, 2025)

Endophytic Beauveria bassiana promotes sunflower growth and confers resistance against sclerotinia disease - Li Sui; Yang Lu; Huiping Yang; Zhiming Liu; Li Wang; Xiaowei Zou; Qiyun Li; Zhengkun Zhang (BioControl, 2025)

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Assessment of Beauveria bassiana for the biological control of corn borer, Ostrinia furnacalis, in sweet maize by irrigation application - Mengxia Feng; Yunyue Zhang; Brad Steven Coates; Qian Du; Yuebo Gao; Lili Li; Haibin Yuan; Wei Sun; Xue Chang; Shuxiang Zhou; Yangzhou Wang (BioControl, 2023)
Kernels of sweet maize are directly consumed by humans. This high value crop is grown in arid and semi-arid regions of western Jilin Province, China where trickle irrigation is widely used and larvae of the corn borer, Ostrinia furnacalis Guenée (Lepidoptera: Crambidae), can cause significant kernel damage. Low humidity in arid regions is less conducive to the efficacy of the biological control agent, Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Cordycipitaceae). Simulated semi-arid conditions in greenhouse experiments were conducted comparing B. bassiana application on a granule carrier or in aqueous suspension to sweet maize. Applications of B. bassiana adhered to granules and in suspension reduced O. furnacalis leaf feeding damage, number of boreholes and tunneling length. Treatments with a granular carrier showed the most significant reductions in maize damage when applied once at whorl stage and in combination with a second application at the ear. The greatest reductions in boring and tunneling attributed to these treatments occurred at internodes around the ear. Although reduced damage was greatest following granular compared to aqueous applications, the latter also provided significant reductions in feeding damage compared to controls. This study demonstrates the utility of B. bassiana as a biological control agent for the reduction in damage caused by second-generation corn borer to sweet maize and existing irrigation equipment could be adapted for efficacious aqueous treatments by growers.

Bacterial communities in predatory mites are associated with species and diet types - Jingyi Yan; Bo Zhang; Guiting Li; Xuenong Xu (BioControl, 2021)

Evaluation of four artificial diets on demography parameters of Neoseiulus barkeri - Ya-Ying Li; Jin-Ge Yuan; Ming-Xiu Liu; Zi-Hui Zhang; Hai-Wei Zhou; Huai Liu (BioControl, 2021)

New potential strains for controlling Spodoptera frugiperda in China: Cordyceps cateniannulata and Metarhizium rileyi - Ye-Ming Zhou; Wen Xie; Jia-Qin Ye; Tao Zhang; Ding-Yin Li; Jun-Rui Zhi; Xiao Zou (BioControl, 2020)

Integrated control of potato late blight with a combination of the photosynthetic bacterium Rhodopseudomonas palustris strain GJ-22 and fungicides - Xin Zhang; Xiaonian Li; Yu Zhang; Yue Chen; Xinqiu Tan; Pin Su; Deyong Zhang; Yong Liu (BioControl, 2020)

Can supplementary food (pollen) modulate the functional response of a generalist predatory mite (Neoseiulus cucumeris) to its prey (Tetranychus urticae)? - Guang-Yun Li; Zhi-Qiang Zhang (BioControl, 2020)

The microbial changes during the biological control of cucumber damping-off disease using biocontrol agents and reductive soil disinfestation - Xinqi Huang; Huiling Cui; Li Yang; Tao Lan; Jinbo Zhang; Zucong Cai (BioControl, 2017)

Chronic, predator-induced stress alters development and reproductive performance of the cotton bollworm, Helicoverpa armigera - Xiaofei Xiong; J. P. Michaud; Zhen Li; Pengxiang Wu; Yanna Chu; Qingwen Zhang; Xiaoxia Liu (BioControl, 2015)

Evaluation of Blattisocius dolichus (Acari: Blattisociidae) for biocontrol of root-knot nematode, Meloidogyne incognita (Tylenchida: Heteroderidae) - Chun-Ling Xu; Yong-Liang Chen; Xue-Nong Xu; Dong-Wei Wang; Hui Xie; En-Dong Wang; Dun-Song Li; Bao-Xin Zhang; Hou-Guo Qin (BioControl, 2014)

Vulnerability window for laying male eggs and superparasitism in producing female offspring of Encarsia sophia on Bemisia tabaci B biotype - Ting-Hui Chen; Min Li; Ji-Hong Wang; Fan Zhang; Yuan-Xi Li (BioControl, 2013)

Biological control of the pinewood nematode Bursaphelenchus xylophilus by application of the endoparasitic fungus Esteya vermicola - Chun Yan Wang; Zhe Ming Fang; Zhen Wang; Dong Liang Zhang; Li Juan Gu; Mi Ra Lee; Lei Liu; Chang Keun Sung (BioControl, 2011)

Effects of intercropping with aromatic plants on the diversity and structure of an arthropod community in a pear orchard - Bei Zhou Song; Hong Ying Wu; Yun Kong; Jie Zhang; Yan Li Du; Jing Hui Hu; Yun Cong Yao (BioControl, 2010)